Security Overhead on a Service with Automatic Resource Management: A Performance Analysis. (9th April 2018) - Batista, Bruno Guazzelli; Kuehne, Bruno Tardiole; Leite Filho, Dionisio Machado; Peixoto, Maycon Leone Maciel
Abstract: As information about clients and businesses is migrating to the cloud, there are growing concerns about how safe this environment is. Furthermore, it is known that as more stringent levels of security are required, the countermeasures, necessary to maintain the security of the system, are subjected to increasing interference on the performance. In the case of cloud computing, it is possible to compensate the overhead generated by the security mechanisms by changing the number of available resources on-the-fly. The aim of this paper is to perform a performance evaluation of a service involving the application of security mechanisms. We considered the change of computing resources during the execution time by means of a dynamic and self-managed module, which was responsible for load balancing, efficient utilization of resources and Quality of Service level assurance. According to the results of the experiments, we verified that the approach in the Vertical environment provided the fulfilment of the requirements defined in the Service Level Agreement, even with security overhead, with slight changes in the service costs.